Controllable preparation method of porous flower-like tin dioxide matrix material assembled by nanoparticles, preparation method of gas sensitive material and application of gas sensitive material

Through the porous flower-like tin dioxide matrix material assembled by nanoparticles, combined with technical means such as copper doping, heterojunction and precious metal modification, the existing n-butanol gas sensitive sensor has solved the problem of high working temperature and poor response performance, and achieved the ability to efficiently detect ppb-level n-butanol gas at low temperatures.

CN119911963APending Publication Date: 2025-05-02HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510120394.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing n-butanol gas-sensitive sensors have high operating temperature, low response value, slow response speed and poor selectivity, making it difficult to effectively detect n-butanol gas at ppb-level concentration.

Method used

A porous flower-like tin dioxide matrix material assembled by nanoparticles was prepared by solvothermal method, calcination and electrochemical plating, etc., to construct heterojunctions and modify precious metal nanoparticles, to regulate the structural morphology of the material to improve gas-sensitive performance.

Benefits of technology

It has achieved good sensing characteristics for n-butanol at a temperature of 80°C, with high response value, short response time, high selectivity, and detectable n-butanol gas at ppb-level concentration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911963A_ABST
    Figure CN119911963A_ABST
Patent Text Reader

Abstract

The invention relates to a controllable preparation method of a porous flower-shaped tin dioxide matrix material assembled by nanoparticles, and a preparation method and application of a gas sensitive material, and belongs to the field of gas sensitive materials. The controllable preparation of the nano-particle assembled porous flower-like stannic oxide-based gas sensitive material is realized by adopting a solvothermal method, a calcining method, a chemical plating method and the like. The material is of a 3D flower-shaped structure which is uniform in size and has the diameter of about 5 microns, the flower-shaped structure is composed of 2D sheet-shaped petals, and basic units forming the sheet-shaped petals are SnO2 particles with the diameter of about 40 nanometers. On one hand, the unique hierarchical porous morphology structure has a large specific surface area, and can provide more surface active sites; on the other hand, more pores are beneficial to transmission and diffusion of gas molecules on the surface of the material. In addition, the n-butyl alcohol sensing performance of the SnO2-based gas-sensitive material is synergistically enhanced by adopting a plurality of synergistic strategies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of gas-sensitive materials, and in particular relates to a controllable preparation method of a porous flower-shaped tin dioxide matrix material assembled by nanoparticles, a preparation method of a gas-sensitive material and an application thereof. Background Art

[0002] n-Butanol is a colorless, transparent, irritating and anesthetic volatile organic compound (VOC), which is widely used as an extractant, surfactant and organic synthesis intermediate. However, long-term exposure to high-concentration n-butanol vapor can have adverse effects on the human respiratory and nervous systems, and cause adverse reactions such as headaches, dizziness and eye irritation. In addition, n-butanol is a highly flammable and explosive liquid. When high-concentration n-butanol vapor is exposed to open flames or high temperatures, or comes into contact with oxidants, it may cause combustion and explosion. Since n-butanol is one of the biomarkers present in the exhaled gas of lung cancer patients, lung cancer screening through breath detection has the advantages of being fast, low-cost and contactless. Therefore, the development of a high-performance n-butanol sensor is of great significance to ensure industrial production safety and protect human life and health.

[0003] Metal oxide semiconductors as gas-sensitive materials have the advantages of simple synthesis, low production cost, and adjustable sensing performance. Among metal oxide semiconductors, SnO2 has broad application prospects in the field of n-butanol gas sensing due to its good environmental compatibility, good thermal stability, and low cost. At present, there have been many reports on metal oxide semiconductor gas sensors for n-butanol gas detection. Although these studies have made proud progress in gas detection, however, existing n-butanol gas sensors generally require an operating temperature above 160°C, and there is still room for improvement in performance indicators such as response value, response time, and selectivity.

[0004] The structural morphology of metal oxide semiconductor materials has a significant impact on their gas sensing properties. High specific surface area and high porosity can provide more surface active sites and are conducive to the diffusion and adsorption of gases. Therefore, developing a controllable preparation process for tin dioxide matrix materials with high specific surface area and high porosity is of great significance for achieving efficient detection of n-butanol. In addition, strategies such as metal ion doping, heterojunction construction and noble metal modification can be used to further improve the gas sensing properties of metal oxide semiconductors and reduce the optimal operating temperature of gas sensors. Summary of the invention

[0005] In order to solve the problems of high operating temperature, low response value, slow response speed and poor selectivity of SnO2-based gas sensors for n-butanol detection, the present invention provides a controllable preparation method of a porous flower-shaped tin dioxide matrix material assembled by nanoparticles, a preparation method of a gas-sensitive material and its application. The gas-sensitive sensor prepared based on the gas-sensitive material can have good sensing characteristics for n-butanol at a temperature of 80°C, and its performance indicators such as response value, response time and selectivity are excellent, and n-butanol gas at a concentration of ppb can be detected. In addition, the gas-sensitive coating obtained by mixing the gas-sensitive material with ethanol can be directly coated on the surface of a ceramic tube prefabricated with electrodes to directly prepare a gas-sensitive sensor, which has the characteristics of simple process and low cost and is suitable for mass production.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A controllable preparation method of a porous flower-shaped tin dioxide matrix material assembled by nanoparticles comprises the following steps:

[0008] Step 1, dissolving thioacetamide and SnCl4·5H2O in isopropanol and stirring to obtain solution A; the ratio of thioacetamide, SnCl4·5H2O and isopropanol is 0.01-0.02g:0.01-0.02g:1mL;

[0009] Step 2, adding CuCl2 to solution A and stirring evenly to obtain solution B; the mixing ratio of CuCl2 and isopropanol is 0-1 mg:1 mL;

[0010] Step 3: Transfer solution B to a stainless steel autoclave lined with polytetrafluoroethylene, place it in an oven and keep it at 160-200°C for 8-20h for high temperature and high pressure reaction. After the reaction is completed, wash and dry the mixture in the reactor to obtain SnS2, and then place it in a tube furnace and calcine it at 400-800°C for 0.5-4h to obtain a porous flower-like tin dioxide matrix material assembled by nanoparticles. By controlling the amount of the reactant CuCl2, the structural morphology of the porous flower-like material assembled by nanoparticles can be regulated.

[0011] In step 1, the volume ratio of the amount of isopropanol to the capacity of the polytetrafluoroethylene-lined reactor is 2 to 4:5.

[0012] In step 3, ethanol and deionized water are used for washing and centrifugation 2 to 4 times respectively, and then dried in a vacuum drying oven at 50 to 80°C.

[0013] A method for preparing a tin dioxide-based gas-sensitive material comprises the following steps:

[0014] Step 1, adding the tin dioxide matrix material prepared by the above preparation method and sodium citrate into deionized water, and magnetically stirring for 10 minutes in a water bath at 60-80° C. to obtain solution C;

[0015] Step 2, add a certain concentration of silver nitrate solution to solution C, stir in a water bath at 60-80°C for 1-10 hours under light-proof conditions to obtain a suspension, wash the suspension and centrifuge to dry it, and then calcine the dried powder at 100-300°C for 8-36 hours to obtain SnO2 / Ag2S@Ag gas-sensitive material. Wherein " / " means that SnO2 and Ag2S contact to form a heterojunction, and @ means that Ag is on the surface of SnO2 / Ag2S, which partially covers and plays a modifying role. Silver nanoparticles are generated in situ on the surface of the tin dioxide matrix material by chemical plating, and then during the calcination process, the sulfur doped in the tin dioxide matrix (from the SnS2 precursor) reacts with silver to form Ag2S until the sulfur doped in the tin dioxide matrix is ​​exhausted.

[0016] The mass ratio of the tin dioxide matrix material to sodium citrate is 0.2-1:1; the ratio of sodium citrate to deionized water is 0.005-0.01 g:1 mL; the volume ratio of the silver nitrate solution to the sodium citrate solution is 0.2-0.5:1; and the concentration of the silver nitrate solution is 0.001-0.1 mol / L.

[0017] An application of the tin dioxide-based gas-sensitive material prepared by the above preparation method, the application method is: put the SnO2 / Ag2S@Ag gas-sensitive material into a mortar and grind it into powder without agglomeration, drop an appropriate amount of anhydrous ethanol and continue grinding for 1 to 10 minutes to obtain a thick gas-sensitive coating, apply the mixed gas-sensitive coating on the surface of the ceramic tube, repeat the coating several times after the coating is dried, and assemble the heating resistance wire with the ceramic tube to obtain the SnO2 / Ag2S@Ag gas sensor. The structural form of the gas sensor is the same as that of the prior art, and the difference between the present invention and the prior art lies in the difference in gas-sensitive materials.

[0018] The mixing ratio of the powder and anhydrous ethanol is 0.1-0.5 g:1 mL.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention adopts solvothermal method, calcination, chemical plating and other methods to realize the controllable preparation of a porous flower-shaped tin dioxide-based gas-sensitive material assembled by nanoparticles. The tin dioxide matrix material prepared by this method presents a 3D flower-like structure with uniform size and a diameter of about 5 microns. The flower-like structure is composed of 2D flaky petals, and the basic unit constituting the flaky petals is SnO2 particles with a diameter of about 40 nanometers. Its unique hierarchical porous morphology has a large specific surface area on the one hand, which can provide more surface active sites; on the other hand, more pores are conducive to the transmission and diffusion of gas molecules on the surface of the material. This unique structure provides a good foundation for gas sensing. In addition, by controlling the amount of CuCl2 in the reaction raw materials, the number of petals of the micron flower can be effectively regulated to obtain an ideal porous flower-like structure.

[0021] 2. The present invention adopts a variety of synergistic strategies such as microstructure regulation (porous flower-like structure assembled by nanoparticles), metal doping (copper-doped SnO2), construction of heterojunction (SnO2 / Ag2S heterojunction) and noble metal modification (Ag nanoparticles) to synergistically enhance the n-butanol sensing performance of SnO2-based gas-sensitive materials. Therefore, the optimal operating temperature of the n-butanol detection of the gas sensor based on copper-doped SnO2 / Ag2S@Ag material is as low as 80°C, and the response value to 50ppm n-butanol (the response value is defined as Ra / Rg, that is, the ratio of the sensor's resistance in air to its resistance in the target gas) is 1136. In addition, the sensor has a fast response time (6s), high selectivity for interfering gases, good long-term stability and ppb-level detection capability.

[0022] 3. The preparation method adopted in the present invention has the advantages of simple process, low cost, and applicability to mass production. It can be flexibly applied to different fields and has broad application prospects in the fields of small breath detection equipment, volatile organic compound leakage alarms, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image (SEM) of the undoped SnO2 material prepared in Example 1;

[0024] Figure 2 This is a scanning electron microscope image (SEM) of the copper-doped SnO2 material prepared in Example 2;

[0025] Figure 3 This is a scanning electron microscope image (SEM) of the excess copper-doped SnO2 material prepared in Example 3;

[0026] Figure 4 This is a scanning electron microscope image (SEM) of the copper-doped SnO2 / Ag2S@Ag gas-sensitive material prepared in Example 4;

[0027] Figure 5 This is a schematic diagram of the structure of the copper-doped SnO2 / Ag2S@Ag gas sensor prepared in Example 5;

[0028] Figure 6 This is a line graph of the response values ​​of the copper-doped SnO2 / Ag2S@Ag gas sensor prepared in Example 5 to 50ppm n-butanol gas at different operating temperatures;

[0029] Figure 7 This is a dynamic response curve diagram of the copper-doped SnO2 / Ag2S@Ag gas sensor prepared in Example 5 to 50ppm n-butanol gas at an operating temperature of 80°C;

[0030] Figure 8 This is a comparison chart of the response values ​​of the copper-doped SnO2 / Ag2S@Ag gas sensor prepared in Example 5 to different types of gases with a concentration of 50 ppm at an operating temperature of 80°C;

[0031] Fig. 9 These are the response values ​​of the copper-doped SnO2 / Ag2S@Ag gas sensor prepared in Example 5 to different concentrations of n-butanol gas at an operating temperature of 80°C. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] Example 1: Preparation of SnO2 material without copper doping

[0034] 0.98 g of thioacetamide and 1.08 g of SnCl4·5H2O were dissolved in 60 mL of isopropanol and stirred for 10 minutes. Subsequently, the solution was transferred to a 100 mL polytetrafluoroethylene-lined reactor and placed at 180 ° C for 16 hours to obtain SnS2 powder. The obtained powder was then transferred to a tube furnace and heated to 600 ° C for 2 hours to obtain a porous flower-like SnO2 matrix material. Its structural morphology is shown in Figure 2. Figure 1 As shown, it presents a porous flower-like morphology assembled by nanoparticles, and the petals are relatively sparse.

[0035] Example 2: Preparation of copper-doped SnO2 material

[0036] 0.98g of thioacetamide and 1.08g of SnCl4·5H2O were dissolved in 60mL of isopropanol and stirred for 10 minutes. Subsequently, 20mg of CuCl2 was added to the above solution and stirred for 5 minutes. The resulting solution was transferred to a 100mL polytetrafluoroethylene-lined reactor and kept at 180℃ for 16 hours to obtain copper-doped SnS2 powder. The resulting powder was then transferred to a tube furnace, heated to 600℃ for 2 hours to obtain a porous flower-shaped copper-doped SnO2 matrix material. Its structural morphology is as follows Figure 2 As shown, it presents a porous flower-like morphology assembled by nanoparticles with a moderate petal density.

[0037] Example 3: Preparation of Excess Copper-Doped SnO2 Material

[0038] 0.98g of thioacetamide and 1.08g of SnCl4·5H2O were dissolved in 60mL of isopropanol and stirred for 10 minutes. Subsequently, 40mg of CuCl2 was added to the above solution and stirred for 5 minutes. The resulting solution was transferred to a 100mL polytetrafluoroethylene-lined reactor and kept at 180℃ for 16 hours to obtain copper-doped SnS2 powder. The resulting powder was then transferred to a tube furnace, heated to 600℃ for 2 hours to obtain a porous flower-shaped copper-doped SnO2 matrix material. Its structural morphology is as follows Figure 3 As shown, it presents a porous flower-like morphology assembled by nanoparticles, and the density of petals is too high.

[0039] Example 4: Preparation of copper-doped SnO2 / Ag2S@Ag gas-sensitive material

[0040] 0.25 g of the porous flower-shaped copper-doped SnO2 matrix material prepared in Example 2 and 0.5 g of sodium citrate were added to 75 mL of deionized water and stirred in a 70°C water bath for 10 min. Subsequently, 25 mL of 0.01 M silver nitrate solution was added to the above solution and stirred in a 70°C water bath in the dark for 4 h. The resulting suspension was then washed, centrifuged and dried. Finally, the resulting powder was calcined at 200°C for 24 hours to obtain the final copper-doped SnO2 / Ag2S@Ag gas-sensitive material. Its structural morphology is as follows Figure 4 shown.

[0041] Example 5: Preparation of copper-doped SnO2 / Ag2S@Ag gas sensor

[0042] 20 mg of the copper-doped SnO2 / Ag2S@Ag material obtained in Example 4 was placed in a mortar and ground until there was no agglomeration in the powder. Two drops of anhydrous ethanol were added and the grinding was continued for 2 minutes to obtain a thick gas-sensitive coating. The mixed gas-sensitive coating was applied to the surface of the ceramic tube. After the coating was dried, the coating was repeated several times. The heating resistance wire was assembled with the ceramic tube to obtain a copper-doped SnO2 / Ag2S@Ag gas sensor. The schematic diagram of the gas sensor structure is shown in FIG. Figure 5 shown.

[0043] Figure 6 This is a line graph of the response values ​​of the copper-doped SnO2 / Ag2S@Ag gas sensor prepared in Example 5 to 50ppm n-butanol gas at different operating temperatures; the test results show that the optimal operating temperature of the sensor is 80°C, and under this condition the response value to 50ppm n-butanol is as high as 1136;

[0044] Figure 7 This is a dynamic response curve of the copper-doped SnO2 / Ag2S@Ag gas sensor prepared in Example 5 to 50ppm n-butanol gas at an operating temperature of 80°C; the test results show that copper-doped SnO2 / Ag2S@Ag has a fast response speed at the optimal operating temperature of 80°C, and the response time to 50ppm n-butanol is 6s.

[0045] Figure 8 This is a comparison chart of the response values ​​of the copper-doped SnO2 / Ag2S@Ag gas sensor prepared in Example 5 to different types of gases with a concentration of 50 ppm at an operating temperature of 80°C; the test results show that the response value of the copper-doped SnO2 / Ag2S@Ag sensor to n-butanol is more than 9 times that of other test gases, so the sensor has good selectivity.

[0046] Fig. 9 The response values ​​of the copper-doped SnO2 / Ag2S@Ag gas sensor prepared in Example 5 to different concentrations of n-butanol gas at an operating temperature of 80°C; the test results show that the response value of the copper-doped SnO2 / Ag2S@Ag sensor to 0.1ppm n-butanol is 3.61, proving that the sensor can be used for ppb-level low-concentration n-butanol detection.

[0047] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A controllable preparation method of a porous flower-like tin dioxide matrix material assembled by nanoparticles, characterized in that: The following steps are involved: Step 1, dissolving thioacetamide and SnCl4·5H2O in isopropanol and stirring to obtain solution A; the ratio of thioacetamide, SnCl4·5H2O and isopropanol is 0.01-0.02g:0.01-0.02g:1mL; Step 2, adding CuCl2 to solution A and stirring evenly to obtain solution B; the mixing ratio of CuCl2 and isopropanol is 0-1 mg:1 mL; Step 3: Transfer solution B to a reactor and keep it at 160-200° C. for 8-20 hours. After the reaction is completed, wash and dry the mixture in the reactor, and calcine the obtained powder at high temperature to obtain a porous flower-like tin dioxide matrix material assembled by nanoparticles.

2. The preparation method according to claim 1, characterized in that: In step 1, the volume ratio of the amount of isopropanol to the capacity of the reactor is 2 to 4:

5.

3. The preparation method according to claim 1, characterized in that: In step 3, ethanol and deionized water are used for washing and centrifugation 2 to 4 times respectively, and then dried in a vacuum drying oven at 50 to 80°C.

4. The preparation method according to claim 1, characterized in that: In step 3, the temperature of high temperature calcination is 400~800℃, time is 0.5~4h.

5. A method for preparing a tin dioxide-based gas-sensitive material, characterized in that: The following steps are involved: Step 1, adding the tin dioxide matrix material prepared by the preparation method according to any one of claims 1 to 4 and sodium citrate into deionized water, and stirring them magnetically in a water bath to obtain a solution C; Step 2: Add the silver nitrate solution to solution C, stir in a water bath under light-proof conditions to obtain a suspension, wash the suspension, centrifuge and dry it, and then calcine the dried powder to obtain the SnO2 / Ag2S@Ag gas-sensitive material.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the tin dioxide matrix material to sodium citrate is 0.2-1:1; the ratio of sodium citrate to deionized water is 0.005-0.01 g:1 mL; the volume ratio of the silver nitrate solution to the sodium citrate solution is 0.2-0.5:1, and the concentration of the silver nitrate solution is 0.001-0.1 mol / L.

7. The preparation method according to claim 5, characterized in that: In step 1 and step 2, the water bath temperature is set to 60-80° C.; the stirring time under light-proof conditions is 1-10 hours.

8. The preparation method according to claim 5, characterized in that: In step 2, the calcination temperature is 100 to 300° C., and the calcination time is 8 to 36 hours.

9. An application of a tin dioxide-based gas-sensitive material prepared by the preparation method according to claims 5-8, characterized in that: The application method is as follows: grind the SnO2 / Ag2S@Ag gas-sensitive material into powder, drop anhydrous ethanol into it and continue grinding to obtain a thick gas-sensitive coating, apply the gas-sensitive coating on the surface of the ceramic tube, repeat the coating several times after the coating is dry, and assemble the heating resistance wire with the ceramic tube to obtain a gas sensor.

10. The use according to claim 9, characterized in that: The mixing ratio of the powder and anhydrous ethanol is 0.1-0.5 g:1 mL.